Presenting a model for predicting marital boredom based on differentiation, emotional intelligence and mental health mediated by resilience in couples - Mehdigholi, Mohamadreza; Dokanei fard, Farideh; Jahangir, Pantae (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to evaluate the fit of the prediction model of marital burnout based on differentiation, emotional intelligence and mental health mediated by resilience in couples. Method: The research method was correlational, structural equation modeling type. The statistical population included all couples referring to family counseling centers in District 1 of Tehran in the second half of July to the end of September 2021, in which 248 couples (124 males and 124 females) were selected by non-random sampling method. They were evaluated using the Marital Burnout Scale (Pines, 1996), Emotional Intelligence (Shut et al., 1998), Resilience (Connor & Davidson, 2003), and Differentiation of Self Questionnaire (Skowron and Dandy, 2003) and General Health Questionnaire (Goldberg & Hiller, 1972) were evaluated. Results: obtained from the evaluation of the proposed model by structural equation using SPSS23 and Smart PLS3 software showed that the model fit indices have a desirable level. There is a significant relationship between differentiation (P< 0.05) and mental health (P